On the Electro-Chemo-Mechanical Coupling in Solid State Batteries and its Impact on Morphological Interface Stability - Ganser, Markus (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2021)
Solid state batteries with a lithium metal electrode are considered the next generation of high energy battery technology. Unfortunately, lithium metal is prone to harmful protrusion or dendrite growth which causes dangerous cell failure. Within this work the problem of protrusion growth is tackled by deriving a novel electro-chemo-mechanical theory tailored for binary solid state batteries which is then used to discuss the impact of mechanics on interface stability by numerical studies.